2005
DOI: 10.1074/jbc.m502222200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Intracellular Fas Ligand (FasL) Domain to the Adaptor Protein PSTPIP Results in a Cytoplasmic Localization of FasL

Abstract: The tumor necrosis factor family member Fas ligand (FasL) induces apoptosis in Fas receptor-expressing target cells and is an important cytotoxic effector molecule used by CTL-and NK-cells. In these hematopoietic cells, newly synthesized FasL is stored in specialized secretory lysosomes and only delivered to the cell surface upon activation and target cell recognition. FasL contains an 80-amino acid-long cytoplasmic tail, which includes a proline-rich domain as a bona fide Src homology 3 domain-binding site. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 43 publications
1
40
0
1
Order By: Relevance
“…In addition, to compare the relative proportion of raftlocalized FasL, we chose HEK293 cell clones with similar cell surface expression levels of full-length, wild-type FasL, FasL delta 1-40, or FasL delta 1-80 ( Figure 3) because deletion of the intracellular domain has been shown to result in increased levels of cell surface FasL. 51 The 293 cell clones were subjected to biochemical raft separation by Brij 98 solubilization and sucrose gradient. Figure 3 illustrates that both deletion mutants were severely impaired in their raft localization.…”
Section: Intracellular Fasl Domain Is Essential For the Partitioning mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to compare the relative proportion of raftlocalized FasL, we chose HEK293 cell clones with similar cell surface expression levels of full-length, wild-type FasL, FasL delta 1-40, or FasL delta 1-80 ( Figure 3) because deletion of the intracellular domain has been shown to result in increased levels of cell surface FasL. 51 The 293 cell clones were subjected to biochemical raft separation by Brij 98 solubilization and sucrose gradient. Figure 3 illustrates that both deletion mutants were severely impaired in their raft localization.…”
Section: Intracellular Fasl Domain Is Essential For the Partitioning mentioning
confidence: 99%
“…We first transfected Fas-deficient Jurkat cells (J16 Rapo ref) with fulllength FasL or delta 1-40 FasL. Because deletion of the intracellular FasL domain increases FasL localization to the cell surface, 51 we again selected these clones for comparable FasL cell surface expression ( Figure 5D, bottom panel). When we compared their behavior in coculture experiments with the Fas-expressing JH6.2 Jurkat target cells, we found that the killing capacity of FasL delta 1-40 was significantly lower than that of full-length FasL ( Figure 5D, upper panel).…”
mentioning
confidence: 99%
“…Different Src homology 3 (SH3)-or WW-domain-containing proteins have been reported to bind to the FasL proline-rich domain in various assays, 1 among them members of the Fes/CIP4 homology/SH3 protein family, which regulate subcellular FasL distribution. 14,15 Nonetheless, the functional significance of the reported interactions for FasL reverse signaling remains unclear.…”
mentioning
confidence: 99%
“…Chimeric receptors based on hFasL did not express well (data not shown) and thus the TM version was designed in an attempt to obtain better expression levels. As indicated in Figure 1A, hFasL-TM is devoid of several putative signaling motifs including a: casein kinase I site (SSASS), 42 a proline motif, which in some cells sequester FasL to a vesicle compartment, 43,44 and MMP-7 site (ELAELR). 45 Figure 1B is a schematic linear representation of the full-length chimeric proteins with the mammalian portion (cytosolic, transmembrane domain, and short extracellular linker) shown fused to the non-mammalian extracellular domain.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins have been extensively characterized [34][35][36][37][38][39][40][41][42][43][44][45][46][47] and are known to be expressed on cancer cells. [48][49][50] The available detailed amino acid sequence information as well as expression patterns of altered native forms; e.g., truncated and mutated, of these two receptors [37][38][39][43][44][45]51 was crucial to our considerations of which alterations to the native sequences might give the best expression alternatives (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%